2012
DOI: 10.1071/rd12039
|View full text |Cite
|
Sign up to set email alerts
|

β-Nerve growth factor is a major component of alpaca seminal plasma and induces ovulation in female alpacas

Abstract: Ovulation in camelids is induced by an unidentified protein in the seminal plasma of the male termed 'ovulation-inducing factor'. This protein has been reported to be a 14-kDa protein under reducing conditions, which, when purified from seminal plasma, induces ovulation in llamas. The identification of this protein and investigation of its potential to induce ovulation in camelids may aid the development of protocols for the induction of ovulation. In the present study, alpaca seminal plasma proteins were sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 26 publications
1
37
0
3
Order By: Relevance
“…However, an induced ovulation mechanism has been demonstrated in alpacas and other camelids (see Adams et al, 2005), and the presence of a potent ovulation-induced factor has been described in the seminal plasma of alpacas and llamas that elicited a surge in the circulating concentrations of LH and induced a luteotropic response (Kersahw-Young et al, 2012). The existence of this factor may be a specific evolutionary mechanism, and it is possible that the hypothalamic regulation of reproduction in alpacas could be different from that of other mammalian species.…”
Section: Functional Considerationsmentioning
confidence: 98%
“…However, an induced ovulation mechanism has been demonstrated in alpacas and other camelids (see Adams et al, 2005), and the presence of a potent ovulation-induced factor has been described in the seminal plasma of alpacas and llamas that elicited a surge in the circulating concentrations of LH and induced a luteotropic response (Kersahw-Young et al, 2012). The existence of this factor may be a specific evolutionary mechanism, and it is possible that the hypothalamic regulation of reproduction in alpacas could be different from that of other mammalian species.…”
Section: Functional Considerationsmentioning
confidence: 98%
“…The ovulation-inducing factor (OIF) present in the seminal plasma recently found to be identical to b-nerve growth factor (b-NGF) [5,6], consistently induced ovulation in camelid species when administered intramuscularly (reviewed in [8]). Ovulation induced by OIF (NGF) was preceded by a rapid increase in plasma LH concentration similar to that observed after copulation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter (e.g., rabbits, cats, koalas, and camelids), ovulation is triggered in response to mechanical stimulation of the female genital tract during copulation. However, results of several llama and alpaca studies have clearly showed that ovulation is induced by a protein factor present in seminal plasma; i.e., induction of ovulation is related to the effects of a chemical constituent of seminal plasma, not the physical or mechanical stimulation of copulation [1][2][3][4][5][6]. The results of a recent study supported this concept; female llamas mated with a urethrostomized male ovulated at a significantly lower rate (16%) than those mated with an intact male [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that all camelids are induced ovulators [1]. Ovulation is induced by the combined inflammatory response to mating and the intrauterine deposition of ß-nerve growth factor present in seminal plasma [2,3]. Follicular dynamics are therefore variable depending on whether the female has been induced to ovulate or not.…”
Section: Introductionmentioning
confidence: 99%